Quantification of horizontal force for the EXER-GENIE® resisted sprint training device - Ghigiarelli, J. J.; Ferrara, K. J.; Yang, Y.; Abrechsten, J. D.; Barat, V. M.; Sell, K.; Gonzalez, A. M. (Frontiers in Sports and Active Living, 2023)
Sport performance coaches use a range of modalities to apply a horizontal force (Fh) to athletes during resisted sprint training (RST). These modalities include parachutes, weighted vests, pulley devices, motored tethered devices, and, most notably, weighted sleds. Despite the widespread use of these devices, the resistance forces of the pulley devices have not been evaluated for reliability and accuracy. Therefore, the primary aim of this study is to quantify the Fh of a commercially available pulley device (EXER-GENIE®) and determine how resistance force is related to the load settings on the device. The secondary aim is to identify the differences in the Fh values between three EXER-GENIE® devices that use 36 m and 60 m ropes. The Fh values in the Newtons (N) of the three EXER-GENIE® devices were analyzed using a motorized winch, a lead acid battery, and an S-beam load cell. Four 10 s winch-driven trials were performed using 15 different EXER-GENIE® loads, ranging from 0.028 kg to 3.628 kg, employing two different 36 m devices and one 60 m device. The mean ± standard deviation for Fh was reported across the four trials for each load setting. All devices produced similar Fh values across lighter load settings (loads =0.141 kg). However, at heavier loads (loads =0.226 kg), the 60 m device had Fh values 50-85 N greater than those of the 36 m device. The coefficient of variation across the four trials was extremely high at light loads but sharply decreased to <10% at heavy loads. Absolute reliability was high for each device [intraclass correlation coefficient (ICC) = 0.99]. A regression analysis for Fh values and EXER-GENIE® load indicated a strong positive relationship between load and Fh values across all devices (R2 = 0.96-0.99). Caution should be exercised when using identical loads on the different-length pulley devices, as the 60 m device produced greater Fh values than the 36 m devices at load settings higher than 0.226 kg. These results can provide coaches and practitioners with a better understanding of the magnitude of resistance that is applied when prescribing EXER-GENIE® devices for higher training loads.